DESIGN OF COST EFFECTIVE HOME MODEL AND ITS INFLUENCE IN LOW SOCIOECONOMIC GERIATRIC RURAL POPULATION - PranjaliGosavi,; S ANAND, (International Journal of Psychosocial Rehabilitation, 2020)
This study was undertaken with an aim to determine the cost effective rural home modification and its influence on instrumental activities of daily living (IADL) and older people quality of life. In the present study 35 subjects with age group between 65 - 80 years. There were 17 males and 18 females. The optimal modifications have been designed and administered the elderly family in possible ways. The pre and post treatment values were measured and documented by using older people quality of life scale (OPQOL - 35), instrumental activities of daily living scale(IADL), and geriatric depression scale (GDS).Statistical analysis was done by using instat software in which Wilcoxon Matched Pairs signed ranks test were used for the analysis. Statistical analysis revealed that there was extremely significant difference between pre and post values of older people quality of life scale, instrumental activities of daily living scale, and geriatric depression scale (p value < 0.0001). All the monitoring tools showed significant difference post treatment. Conclusion- that the cost effective rural home modification has shown good progression in instrumental activities of daily living (IADL) and the Quality of Life in elderly.